The sharing economy in the context of reducing food waste in the catering market - Hanus, Paweł; Kogut, Łukasz; Adamczyk, Greta; Jaworska, Grażyna (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2025)
The purpose of the study was to analyse the importance of the sharing economy as a tool to reduce food waste in the gastronomy sector. The theoretical part discusses the concept of the sharing economy, food sharing, and the zero waste approach in the context of sustainable consumption. The empirical part included a survey conducted among consumers (n=108) and in-depth interviews with representatives of gastronomic establishments. The results indicate that consumers are significantly more willing to use the services offered by restaurants involved in food waste reduction activities. Restaurant owners perceive food-sharing applications primarily as ideological and image-building tools, as well as a means of reducing financial losses, at the same time pointing out the key barriers to their implementation.

Celem pracy była analiza znaczenia ekonomii współdzielenia jako narzędzia ograniczania marnowania żywności w sektorze gastronomicznym. W części teoretycznej omówiono istotę sharing economy, foodsharingu oraz koncepcji zero waste w kontekście zrównoważonej konsumpcji. Część empiryczna obejmowała badanie ankietowe przeprowadzone wśród konsumentów (n=108) oraz wywiady pogłębione z przedstawicielami lokali gastronomicznych. Uzyskane wyniki wskazują, że konsumenci są zdecydowanie bardziej skłonni korzystać z usług restauracji podejmujących działania na rzecz redukcji strat żywności. Restauratorzy postrzegają aplikacje foodsharingowe głównie jako narzędzia ideologiczne i wizerunkowe, a także jako sposób ograniczania strat finansowych, jednocześnie wskazując na istotne bariery ich wdrażania.
Ekonomia współdzielenia w kontekście ograniczenia marnowania żywności na rynku usług gastronomicznych
Keywords: sharing economy; food sharing; food waste; zero waste; gastronomy; ekonomia współdzielenia; foodsharing; marnowanie żywności; gastronomia